An Analysis of Walking Permeability, Walking Effort, and the Walkability Index: A Case Study of the Dayang Sumbi Entrance, Institut Teknologi Bandung (ITB) - Ammar Asyraf; Edlin Al Khuzaifah Hasbi; Irwandra Septiadi (Inersia: Jurnal Teknik Sipil, 2026)
Human mobility in Bandung City cannot be avoided. Congestion and travel distance make walking a popular choice. Accessibility is measured by walking distance (400–800 m) and walking time (10–15 minutes). Route characteristics affect walking effort, determining accessibility quality. Ganesha Campus ITB, especially Dayang Sumbi Gate, has high pedestrian traffic. This study assesses walkability using Permeability Framework, Walking effort approach, and Walkability Index. Results shows the route to McDonald's Dago via Jl. Sumur Bandung has the highest Walking Effort and Permeability: 3155 m (normal)–2300.26 m (opposite) and 5.836 (normal)–4.939 (opposite). The best road by walkability index is Jl. Ir. H. Djuanda While the Worsts one is Jl. ITB IX.